Apologizing in English and Indonesian : An Interlanguage Pracmatic Case Study of Students at Muhammadiyah Boarding School Rappang - Sri Fitri Ramadhani; Andi Sadapotto; Nadirah, Nadirah; Hermansyah, Sam; Ibrahim Manda (International Journal of Sustainable Applied Sciences, 2023)
This research uses the qualitative method as the research methodology. This research was conducted to know what How are students ability to apologize and How are the apology strategies of students at the Islamic boarding school.The population in this research were the students of Muhammadiyah boarding school Rappang in this research were 6 students dan 2 Teachers. The data collection method used in this research was an interview. The results showed that most of the Muhammadiyah boarding school Rappang students apologized by addressing the person directly. and they have different strategies in apologizing. Several strategies to apologize to friends that can be done are Express an apology directly, apologize by giving an explanation, apologize by saying responsibility, apologize by offering a fix, and apologize by promising not to do it again.